Seren Taun Guru Bumi Harmony of Islam and Pasundan Culture - Abdurrahman Misno BP (Al-Albab, 2016)
The advent of Islam in Tatar Sunda (West Java) lent a new color to the culture that had previously existed there. The nature of Islam which was friendly to the local culture, made it easy to be accepted by the Sundanese people without bloodshed. The results are a variety of cultural rituals rooted in Sundanese culture yet rich with Islamic culture. Seren Taun Guru Bumi is one of the rituals of the Sundanese people deeply-rooted in the belief of Nyi Pohaci (Dewi Sri) as the goddess of fertility. The involvement of the researcher in this ritual made the data a primary source which is the implementation of Seren Taun Guru Bumi in Sindang Barang Cultural Village, Bogor, West Java. This research shows that the ritual of Seren Taun Guru Bumi is a form of Islamic harmony with the Sundanese culture. Islamic culture assimilates in the frame of Sundanese traditions in Tatar Sunda, in which both are brought together in the ritual as a form of gratitude to God Almighty.